Social responsibility and spiritual intelligence: university students’ attitudes during COVID-19 (2022)
Human behavior during COVID-19 has led to the study of attitude and preferences among the population in different circumstances. In this sense, studying human behavior can contribute to creating policies for integral education, which should consider the convergence between social responsibility and spiritual intelligence. This can lead to the sensitization of practices and attitude modification within society. The purpose of our research was to explore the spiritual intelligence attitudes of university students from the perspective of social responsibility, considering the sociodemographic characteristics of the research subjects during the COVID-19 pandemic. Our research design is quantitative and sectional, due to the use of two quantitative scales. The participants were university students from a city located in south-central Chile. A total of 415 participations were collected, of which 362 applications were valid. Statistically significant differences were found according to gender and age. Women and the student cohort between 18 and 24 years of age placed more importance on spiritual necessities. We thus highlight the necessity to have adequate spaces for spiritual intelligence training given its links with socially responsible behavior and, finally, the development of explanatory studies to determine its causalities. In practice, these results contribute to designing an educational policy on the formation of integral spiritual intelligence for future professionals.